A misunderstood Pope - Juan Bottasso (Universidad Politécnica Salesiana, 2013)
After Pope Benedict´s resignation, the media obsessively highlighted divisions of the Church and the scandals, forgetting that Joseph Ratzinger had sought to preserve the Church´s "common denominator of tradition and dogma". Through a brief analysis on the difficult path Ratzinger had to lead, as part of the Ecumenical Council, in his differences with the theology of liberation, and his reluctance later as Pope to blindly leap into modernity, this article points out Ratzinger´s efforts to keep the Church unified. Ratzinger belonged to the progressive wing of the Council, however, his work was misunderstood for having to maintain order in a world marked by 1968´s social revolution, the Cold War, Marxism, the politicization of religion, and thus having to defend the Church from "self-destruction". This article discusses the reality of Ratzinger, Pope Benedict XVI, a life dedicated to the Catholic Church in the face of today´s world challenges.